The University and its commitment to PYMES - Zapata, Teonila García (2001)
This article decribes small and micro enterprises (Pymes) of Peru, showing its shortcomings and opportunities based on their evolution and current state, settling down against critically analyze future prospects. In this context, engagement guidelines for passage subsistence level to the level of capital accumulation and growth of small and microempresas.La University and commitment arise with